2018
DOI: 10.3390/educsci8040170
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Evidence-Based Video Modeling for Students with Emotional and Behavioral Disorders

Abstract: This systematic review examined eight studies showing that video modeling (VM) can have a positive and significant effect for students with emotional and behavioral disorders (EBD). Building upon meta-analyses that sought evidence of video-based interventions decreasing problem behaviors of students with EBD in K-12 education, the review examined the standards of the Council for Exceptional Children (CEC) for evidence-based practice as well as additional quality indicators, neglected quality indicators, strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Soares et al (2016) classified token economies as an EBP. Finally, Seok et al (2018) reviewed video modeling and identified the practice as evidence-based. The remaining 12 practices (60%) did not have sufficient evidence to be classified as evidence-based.…”
Section: Resultsmentioning
confidence: 99%
“…Soares et al (2016) classified token economies as an EBP. Finally, Seok et al (2018) reviewed video modeling and identified the practice as evidence-based. The remaining 12 practices (60%) did not have sufficient evidence to be classified as evidence-based.…”
Section: Resultsmentioning
confidence: 99%
“…Most promising is the use of multiple forms of VM with students with EBD, particularly in terms of VM’s capacity to increase student classroom engagement. For instance, Losinski et al (2016) and Seok et al (2018) found that VM and its variants demonstrated large effects for reducing challenging behaviors of students with EBD.…”
Section: Review Of the Vm Evidence Basementioning
confidence: 99%
“…The research base for VM demonstrates that it is a powerful and effective intervention to support students in a wide variety of contexts, including students with emotional and behavioral disorders (EBD; Losinski et al, 2016; Mason et al, 2013; Seok et al, 2018; Shukla-Mehta et al, 2010). Recently, several literature and meta-analytic reviews have been conducted to measure the effectiveness of the practice on a diverse body of students.…”
Section: Review Of the Vm Evidence Basementioning
confidence: 99%
See 1 more Smart Citation
“…Self-observation is a relevant method to promote behaviour change, because it influences self-confidence, self-awareness, and self-efficacy, and has an emotional impact [10,11]. Self-observation has been evaluated in interventions focused on behaviour change, such as in the treatment of attention deficit hyperactivity disorder, autism, emotional disturbances, speaking ability, and so on [12], and for skill acquisition in sport [13,14]. Moreover, self-observation has been applied in different training programs to improve the interaction skills of professionals [15], and to increase one's own teaching [16].…”
Section: Introductionmentioning
confidence: 99%